English Learning Planning Management in the Time of Pandemic Covid-19: Case of UPB UIN Antasari - Fitria Mumtazah; Jarkawi; Muhammad Yuliansyah (ELT in Focus, 2022)
The purpose of this study is to describe the English language learning management plan carried out by UPB (Unit Pengembangan Bahasa) UIN (Universitas Islam Negeri) Antasari during the Covid-19 pandemic, as well as to analyze this English language learning process carried out by UPB UIN Antasari during the Covid-19 pandemic through a learning management plan perspective. This research is a qualitative field research, where data is collected through observation during the teaching-learning process, interviews with UPB managers, teaching staff (tutors), and program participants (students), as well as document study of textbooks and other learning documents. The author then validated the data using triangulation techniques, and analyzes them descriptively. The results showed that during the Covid-19 pandemic, UPB had implemented learning management plan in its intensive English learning. UPB has carried out preparations for the effective week according to the academic calendar, as well as making annual programs and semester programs in the form of textbooks. In terms of honorarium, UPB is even above the generally accepted standard, due to the consistency of tutor fees even in the midst of the Covid-19 pandemic. The main drawback of the implementation of learning management plan by UPB is the absence of lesson plan documents and syllabus, However, the absence of these two learning documents does not necessarily make this intensive program a failure, because UPB has provided textbooks to replace it. Based on the final exam results, it is proven that this intensive program is successful in improving students' English skills.